2002
DOI: 10.1111/j.1582-4934.2002.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐stimulatory and adhesion molecules of dendritic cells in rheumatoid arthritis

Abstract: Dendritic cells (DCs) in the rheumatoid arthritis (RA) joint mediate the immunopathological process and act as a potent antigen presenting cell. We compared the expression of co‐stimulatory and adhesion molecules on DCs in RA patients versus controls with traumatic joint lesions and evalulated the correlation between the immunophenotypical presentation of DCs and the clinical status of the disease. Samples of peripheral venous blood, synovial fluid (SF) and synovial tissue (ST) were obtained from 10 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Stained cells were washed twice with PBS/bovine serum albumin and analysed using an EPICS XL flow cytometer and expo 32 software (Beckman Coulter, Fullerton, CA). Compared with the THP‐1 cells, the iDC and mDC have differential expression of CD80, CD83, CD86 and HLA‐DR, with iDC being CD80 hi , CD83 lo , CD86 lo , HLA‐DR lo , and mDCs phenotypically described by CD80 hi , CD83 hi , CD86 hi , HLA‐DR hi compared with the original THP‐1 cells (4, 22, 32).…”
Section: Methodsmentioning
confidence: 98%
“…Stained cells were washed twice with PBS/bovine serum albumin and analysed using an EPICS XL flow cytometer and expo 32 software (Beckman Coulter, Fullerton, CA). Compared with the THP‐1 cells, the iDC and mDC have differential expression of CD80, CD83, CD86 and HLA‐DR, with iDC being CD80 hi , CD83 lo , CD86 lo , HLA‐DR lo , and mDCs phenotypically described by CD80 hi , CD83 hi , CD86 hi , HLA‐DR hi compared with the original THP‐1 cells (4, 22, 32).…”
Section: Methodsmentioning
confidence: 98%
“…In an autoimmune disease such as rheumatoid arthritis, the presence of large numbers of activated DCs in the affected synovium [ 12 , 13 ] suggests that these cells present local autoantigens to cognate effector T cells in situ [ 14 , 15 ]. However, studies on pathological specimens present a static picture, usually of established disease, and there is little information available about the kinetics of recruitment of DC precursors in the early rheumatoid lesion.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The interaction between CD2 and CD58 has significant importance in autoimmune diseases such as rheumatoid arthritis (RA). 57 The results of large genome-wide association studies (GWAS) suggest that more than 30 loci are involved in RA pathogenesis, and CD2 as well as CD58 is important. 6 Previous reports have indicated that inhibition of the CD2 and CD58 interactions using a LFA-3 fusion protein (alefacept) inhibits T-cell activation.…”
mentioning
confidence: 99%